PERCENTAGE OF HEPATITIS B AND C AMONG YOUNG ADULT MALES FROM INTERIOR SINDH: Hepatitis B and C among Young Adult Males - Malik, Nasrullah; Butt, Tariq; Mansoor, M. Nasir; Khan, Tahir Ghias; Akbar, Muhammad Sajid; Aslam, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
Objective: Present study was planned to know the seropercentage of Hepatitis C Antibodies and Hepatitis B Surface Antigen in a population based sample of healthy male army/naval recruits from rural Sindh. Design: Laboratory based non-interventional, descriptive study. Place and Duration of study: Conducted at Combined Military Hospital Pano Aqil from 1st January 2006 to 31st October 2006. Patients and Methods: A total of 5237 healthy male recruits from various districts of interior Sind were studied. HBsAg and Anti-HCV were tested by Immunochromatographic assay and positive tests were confirmed by ELISA method. Results: The percentage of anti-HCV was (4.37%) and was (7.39%) for HBsAg. The percentage of HBsAg in districts Nowsheroferoze (10.11%), Ghotki (9.21%) and Khairpur (7.48%) and Anti-HCV (p<0.0001) in districts Nawabshah (9.32%), Khairpur (6.71%) and Ghotki (6.64%) respectively was higher than the other districts. Both the viruses are evenly distributed among the remaining different Districts’ population. Conclusion: There is considerable threat of HBV and HCV in interior Sind. Screening of selected groups and vaccination against Hepatitis B may be considered in these areas. Health education to general public including barbers would be the key for control/prevention of these dreadful diseases.